Sharing riders: How bikesharing impacts bus ridership in New York City - Campbell, Kayleigh B.; Brakewood, Candace (Transportation research. Part A, Policy and practice, 2017)
•This paper aims to estimate the effect of bikesharing on bus ridership.•A difference-in-differences identification strategy is utilized.•The number of docks are used to quantify the intensity of bikeshare near bus routes.•Results indicate a 2.42% decrease in bus trips per thousand docks along a bus route.•People who are not bikeshare members may also be changing their travel behavior. The objective of this research is to quantify the impact that bikesharing systems have on bus ridership. We exploit a natural experiment of the phased implementation of a bikesharing system to different areas of New York City. This allows us to use a difference-in-differences identification strategy. We divide bus routes into control and treatment groups based on if they are located in areas that received bikesharing infrastructure or not. We find a significant decrease in bus ridership on treated routes compared to control routes that coincides with the implementation of the bikesharing system in New York City. The results from our preferred model indicate that every thousand bikesharing docks along a bus route is associated with a 2.42% fall in daily unlinked bus trips on routes in Manhattan and Brooklyn. A second model that also controls for the expansion of bike lanes during this time suggests that the decrease in bus ridership attributable to bikesharing infrastructure alone may be smaller (a 1.69% fall in daily unlinked bus trips). Although the magnitude of the reduction is a small proportion of total bus trips, these findings indicate that either a large proportion of overall bikeshare members are substituting bikesharing for bus trips or that bikesharing may have impacted the travel behavior of non-members, such as private bicyclists. Understanding how bikesharing and public transit systems are interrelated is vital for planning a mutually reinforcing sustainable transport network.